Reduced Movement Variability and Kinematics Changes During a Hand to Head Movement are Associated with Improved Outcome Following Superior Capsular Reconstruction (232). Issue 10 (31st October 2021) - LeVasseur, Clarissa; Kane, Gillian; Hughes, Jonathan; Popchak, Adam; Irrgang, James; Anderst, William; Lin, Albert
Objectives: Patients with irreparable rotator cuff tears (RCT) exhibit functional limitations including limited ability to perform functional tasks such as combing their hair. One viable treatment is superior capsular reconstruction (SCR). SCR has been shown to restore stability of the glenohumeral (GH) joint in cadavers1, but its effect on in vivo scapular and humeral motion is unknown. The aims of this study were to determine the effect of SCR on in vivo scapular and humeral kinematics during a functional hand to head motion and to identify associations between shoulder kinematics and patient-reported outcomes (PROs). We hypothesized that moving the hand to the back of the head would be accomplished by using more GH based movement including rotation and abduction, and less scapular motion after SCR, and there would be a positive correlation between kinematics changes and improved PROs. Methods: Ten patients (8M, 2F, age 63 ± 7 years) with irreparable RCT provided informed consent to participate in this prospective IRB-approved study. American Shoulder and Elbow Surgeon (ASES), Disability of the Arm Shoulder and Hand (DASH), and Western Ontario Rotator Cuff Index (WORC) surveys were completed before (PRE) and 1-year (1YR-POST) after SCR. Participants were seated and instructed to move their hand from their lap to the back of their head while synchronized biplane radiographs of the shoulder were collected PRE and 1YR-POST at 50 images/s for 3 separate trials. Six degree of freedom GH and scapular kinematics were determined with sub-millimeter accuracy by matching subject-specific CT-based bone models of the humerus and scapula to the synchronized radiographs using a validated volumetric tracking technique3. The contributions of humeral abduction, plane of elevation and internal/external (I/E) rotation relative to the scapula, as well as scapular upward rotation, protraction, and tilt, were calculated for each subject before and after SCR. Differences in rotational contributions from PRE to POST were evaluated using a paired t-test. Variability in rotational contributions was characterized by the inter-subject standard deviation in rotational component contributions to the movement. Correlations among changes in the contribution of each rotation component and between the contribution of each rotation component and PROs were evaluated with Pearson's correlation coefficients. Significance was set at p < 0.05 for all tests. Results: No differences in contribution to motion were identified in any of the rotational components from PRE to POST (all p > 0.15, Figure 1). Inter-subject variability in rotational contributions to the movement decreased in 5 of the 6 rotational components from PRE to 1YR-POST (Table 1; Figure 1). The PRE to 1YR POST change in contribution from GH abduction was positively correlated to the change in contribution from GH I/E rotation (Figure 2, R = 0.8, p = 0.001) and negatively correlated to the change in contribution from scapular protraction (Figure 2, R = -0.94, p = 0.001). ASES scores were negatively correlated with abduction contribution PRE (R = -0.65, p = 0.043), and positively correlated with plane of elevation PRE (R = 0.685, p = 0.03). Changes in the plane of elevation contribution were also positively correlated with changes in ASES scores (R = 0.635, p = 0.048). Conclusions: This is the first study to report GH and scapular kinematics when performing the functional task of placing the hand to the back of the head. Changes in contributions to the motion were inconsistent across subjects, making it difficult to find differences from PRE to POST. However, inter-subject variation was reduced following surgery, suggesting the participants' movement strategy converged toward a more similar and possibly more efficient movement pattern following SCR. Increased contributions of glenohumeral rotation and abduction were offset by decreased scapular protraction and indicates SCR affects the contributions from these three rotations, partially supporting our first hypothesis. In addition, increased GH plane of elevation contribution following surgery was associated with improved ASES scores supporting our second hypothesis. This may be consistent with improved glenohumeral kinematics and efficiency of movement during a functional task following SCR. Future work will investigate GH and scapular kinematics in healthy individuals performing the hand to head movement to determine if movement strategy is closer to healthy after SCR.